Tisp40 Induces Tubular Epithelial Cell GSDMD-Mediated Pyroptosis in Renal Ischemia-Reperfusion Injury via NF-κB Signaling - Xiao, Chengcheng; Zhao, Haijun; Zhu, Hai; Zhang, Yingyu; Su, Qiuju; Zhao, Feng; Wang, Renhe (Frontiers in Physiology, 2020)
Renal ischemia-reperfusion injury (IRI) is a major cause of acute kidney injury (AKI). As a transcription factor, the Transcript induced in spermiogenesis 40 (Tisp40) has been found to be involved in renal IRI. However, the role of Tisp40 in tubular epithelial cell (TEC) pyroptosis of renal IRI remains unknown. In this study, we investigated effects of Tisp40 on Gasdermin D (GSDMD)-mediated TEC pyroptosis in renal IRI and underlying molecular mechanisms in I/R-induced kidney by hematoxylin and eosin (HE) staining, Terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL) assay,immunohistochemistry (IHC), reverse transcription-quantitative PCR (RT-qPCR) and western blot analysis in vivo and oxygen-glucose deprivation/reoxygenation (OGD/R)-stimulated TCMK-1 cells by lactate dehydrogenase (LDH) release assay, CCK-8 assay,enzyme-linked immunosorbent assay (ELISA), flow cytometric analysis, immunofluorescence staining,RT-qPCRand western blot analysis in vitro. We found that the levels of Tisp40 and GSDMD-N expression increased gradually, and peaked at 30 min ischemia/24 h reperfusion in vivo and 24 h OGD/R/6 h reoxygenation in vitro, simultaneously, the levels of TEC pyroptosis and renal injury were correspondingly increased. The data of Pearson’s correlation analysis showed that the expression of Tisp40 and GSDMD-N was positively correlated. Furthermore, Tisp40 overexpression aggravated TEC pyroptosis rate and increased the expressions of related proteins, including GSDMD-N, NLRP3, caspase-1, IL-1β, and IL-18 in the OGD/R-stimulated TCMK-1 cell line, whereas the opposite occurred in cells treated with small interfeing RNA (siRNA) targeting Tisp40. Tisp40-deficient mice showed attenuated renal IRI and pyroptosis compared with wild-type mice. In addition, Tisp40 knockout remarkably decreased the levels of GSDMD-N, IL-1β, IL-18, NLRP3, and caspase-1 expression, and alleviated renal pyroptosis induced by I/R. Importantly, Tisp40 overexpression significantly increased TECs pyroptosis via p-p65 activation, however, the effects of Tisp40 overexpression were partially blocked by parthenolide (PTL). Collectively, our findings provide insight into the mechanism of how Tisp40 regulated GSDMD-mediated pyroptosis in renal IRI.